AN INVESTIGATION OF LEARNING MANAGEMENT MODEL TO CREATE RELIGIOUS HEIRS OF THE THAI BUDDHIST SANGHA - Suvuddhiko (Boonsaner), Phramaha Woot; Siriwan, Intha; Ngamprakhon, Sin; Chirakulo (Jongsakulsiri), Phramaha Padet (Journal of Educational Review Faculty of Education in MCU, 2021)
This research article aimed to examine learning management model for creating religious heirs of the Thai Buddhist Sangha. Mixed methods research was used and there were 3 research steps as follows: Step 1: Study the condition of learning management for creating religious heirs of the Thai Buddhist Sangha by interviewing 10 key informants, and the data was analyzed by content analysis. Step 2: Create a learning management model for creating religious heirs of the Thai Buddhist Sangha using focus group discussion with 17 experts, and data was analyzed by content analysis. Step 3: Examine and propose a learning management model for creating religious heirs of the Thai Buddhist Sangha. It was used to distribute the model assessment form with 200 monks and novices. The data were analyzed by using descriptive statistics such as frequency, percentage, mean and standard deviation. Results of the research found that examination of the learning management model for creating religious heirs of the Thai Buddhist Sangha consisted of part 1 introduction, part 2 learning management process, and part 3 the implementation of the process in actual practice, showed overall in a high level. When considering each aspect, it was found that at the highest level in 2 aspects which were usefulness and correctness, and at a high level in 2 aspects which were feasibility and suitability.